Food addiction and grazing - the role of difficulties in emotion regulation and negative urgency in university students - Ribeiro, Andreia (2023)
University students are a vulnerable population to the development of disordered eating, such as food addiction (FA) and grazing. FA is an emerging concept characterized by an intense desire to eat hyper-palatable foods. Grazing is characterized by the repetitive and unplanned ingestion of food throughout a period of time. Both FA and grazing have been associated with increased scores of negative urgency (NU) and difficulties in emotion regulation (ER). This study aims to evaluate the frequency of FA and grazing in a university population and to test the direct, total, and indirect effects—via FA—of ER and NU on repetitive eating and compulsive grazing. A total of 338 participants responded to a set of psychological measures assessing these variables. Thirty-six (10.7%) participants met the criteria for FA diagnosis and 184 (54.4%) presented grazing. Confirmatory factor analysis showed acceptable fit indexes for the model tested (χ2(1695) = 3167.575; p < 0.001; CFI = 0.955; NFI = 0.908; TLI = 0.953; SRMR = 0.085; RMSEA = 0.051; CI 90% (0.048; 0.053); P[RMSEA ≤ 0.05] = 0.318) and suggested that FA partially mediated the effect of difficulties in ER and NU on grazing, specifically on compulsive grazing. The results indicate that individuals with difficulties in ER and impulse control under negative emotions are more likely to engage in grazing if food addiction scores are higher. These results highlight the importance of assessing these variables, particularly in at-risk populations such as university students.